2015
DOI: 10.1152/jn.00731.2015
|View full text |Cite
|
Sign up to set email alerts
|

Imaging fictive locomotor patterns in larvalDrosophila

Abstract: We have established a preparation in larval Drosophila to monitor fictive locomotion simultaneously across abdominal and thoracic segments of the isolated CNS with genetically encoded Ca2+ indicators. The Ca2+ signals closely followed spiking activity measured electrophysiologically in nerve roots. Three motor patterns are analyzed. Two comprise waves of Ca2+ signals that progress along the longitudinal body axis in a posterior-to-anterior or anterior-to-posterior direction. These waves had statistically indis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
169
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(184 citation statements)
references
References 95 publications
15
169
0
Order By: Relevance
“…Intensities of neuronal activation were found to be higher during BW and FW compared to AT and PT. We also confirmed that AT but not other motor patterns shows strongly asymmetric activity as previously reported 13 . It has been known that transition between different motor patterns in behaving larvae is biased 30,31 .…”
Section: Introductionsupporting
confidence: 92%
“…Intensities of neuronal activation were found to be higher during BW and FW compared to AT and PT. We also confirmed that AT but not other motor patterns shows strongly asymmetric activity as previously reported 13 . It has been known that transition between different motor patterns in behaving larvae is biased 30,31 .…”
Section: Introductionsupporting
confidence: 92%
“…However, as described previously 30 , occasionally a spike occurred alongside a coincident trough in GCaMP6m fluorescence in the contralateral motoneuron dendrite (Fig. 4B).…”
Section: The Pnkd3 Mutation Disrupts Cpg Activity In the Larval Ventrsupporting
confidence: 83%
“…The function of pre-motor circuits and motoneurons driving larval locomotion can be interrogated via sharp electrode recordings and ex vivo calcium imaging [29][30][31] . Furthermore, the neuromuscular junction (NMJ) of Drosophila larvae represents a widely studied model glutamatergic synapse in which alterations in neurotransmitter release and/or synaptic plasticity can be readily assessed 32 .…”
Section: Introductionmentioning
confidence: 99%
“…The work presented here also stands in contrast to previous models of larval 673 peristalsis [38,40] and the prevailing hypotheses regarding this phenomenon [15,58] by 674 eschewing any role for intrinsic neural dynamics. Such stereotyped and rhythmic 675 locomotion is widely assumed to be the signature of a central pattern generator (CPG), 676 that is, a neural circuit that intrinsically generates a rhythmic output, and thus 677 determines a particular mechanical trajectory to be followed by the body [59][60][61].…”
mentioning
confidence: 60%